Kajian Ketahanan Aspek Fisik Rumah Bali Aga dalam Merespons Covid-19 Studi Kasus Rumah Adat Desa Pedawa - Made Wina Satria; Km. Deddy Endra Prasandya; Nyoman Ratih Prajnyani Salain (Universitas Sebelas Maret Surakarta, 2022)
The purpose of this study was to formulate criteria and indicators for buildings that have resistance to covid-19, then study the physical aspects of the Pedawa Village traditional house building. This study is a mixed method study that integrates qualitative and quantitative methods. Interpretive criticism were used to formulate the criteria. Measurements with a 1-3 scale and JMP statistical analysis tool were used to formulate the conditions of physical aspects of the Pedawa Village traditional house. The result shows that there are three main criteria for Covid-19 responsive buildings, including utility, layout, and materials. The evaluation of the Pedawa Village traditional houses show that the house meets 12 of the 18 indicators of the covid-19 response house. These indicators include water supply, drainage, building orientation, ventilation direction, distance between buildings, site area, open space, building massing composition, and choice of materials and materials.